Reliability and validity of instrument on academic enhancement support for student-athlete using rasch measurement model - Rozali, Mohd Zulfadli; Puteh, Saifullizam; Nur Yunus, Faizal Amin; Hamdan, Nor Hidayah; Mohd Latif, Hadafi Fitri (2022)
The purpose of this article is to develop and validate an instrument on Academic Enhancement Support for Malaysian student-athletes. The instrument development process began earlier in previous research's stages. Thirty-five questionnaires were distributed to Malaysia Public University student-athletes who competed at the university and state levels. It took a week to collect data, with a 100% return rate and one damaged questionnaire removed. Winstep version 3.69.1.11 was used to conduct three analyses: item-person reliability and separation index, statistical fit, and standardised residual correlation for item dependent. Cronbach's alpha of 0.96 indicates high reliability, with all items displaying a positive value for item polarity. Thirty items were identified as being misfit, five of which were removed and fifteen of which were revised. In the final analysis, ten pairs of items were dictated to be redundant, and ten items were eliminated following selection. In total, 15 items were removed from the instrument, leaving 82 items in the validated version. In conclusion, the instrument developed is a valid instrument capable of validating the student-perception athlete's of the support necessary for academic advancement during actual study.